Psikoedukasi Expressive Writing sebagai Strategi Coping untuk Membangun Resiliensi Emosional Anak Panti Asuhan Wikrama Putra Semarang - Arrayan Mukti; Hana Fitri; Isna Laily Istiqomah; Selfi Ana Andriyanti; Ainnayya Nayla Daffani; Muhammad Fitahul Fikri; Allaiya Talent; Tribuana Tunggal Dewi; Dewi Khurun Aini (Lembaga Pengembangan Kinerja Dosen, 2025)
Children living in orphanages face various psychological pressures, such as the loss of attachment figures, unstable social dynamics, and difficulty expressing emotions adaptively. These conditions require appropriate coping strategies to build emotional resilience. This community service activity utilizes a Service Learning (SL) approach, which integrates academic learning with community service. It aims to provide psychoeducation on emotions and coping strategies, and implements expressive writing as a means of emotional processing. The activity methods included interactive lectures, a pretest and posttest to measure understanding, an expressive writing therapy session, and a reflective interview at the end of the activity. Results showed an increase in understanding of emotions and coping strategies, as evidenced by improved posttest scores. Furthermore, expressive writing helped children express previously suppressed emotions, reduced psychological tension, and fostered a sense of relief, calm, and insight into personal problems. Overall, expressive writing has proven effective as a coping strategy in building emotional resilience in orphanage children, and the Service Learning approach has the potential for sustainable application in psychosocial support programs.